Online information bombardment! How does eWOM on social media lead to consumer purchase intentions?. (14th September 2020) - Khwaja, Muddasar Ghani; Mahmood, Saqib; Jusoh, Ahmad
Social media networks have increased Electronic Word of Mouth (eWOM) conversations which have created numerous opportunities for online businesses. People using social media networks have been able to discuss, evaluate and argue on different products and services with their friends, family and peers. The study aimed to determine the influence of these social media conversations on the consumer purchase intentions. In this regard, Erkan and Evans' (2016) study was extended as an integrated framework of Theory of Reasoned Action (TRA) and Information Adoption Model (IAM). The proposed framework was estimated using Structural Equation Modelling (SEM) on AMOS. Survey method was deployed in which data from 342 respondents were taken who have been involved in online purchasing due to social media influence. The results attained affirmed the established theoretical foundations.